Preliminary Mapping of Mutations Affecting Exonuclease III in Escherichia coli K-12 - Milcarek, Christine (1973)
xthA, a structural gene for exonuclease III in Escherichia coli K-12, is cotransducible with aroD, aroH, and pps.